PENINGKATAN POPULASI DAN PEMANFAATAN AYAM LOKAL BENGKULU MELALUI PENERAPAN TEKNOLOGI MIKRONUTRISI DAN PENETASAN SEDERHANA UNTUK PENINGKATAN PENDAPATAN MASYARAKAT - ., Nurmeiliasari; Putranto, Heri Dwi; Santoso, Urip; Andani, Apri (Dharma Raflesia : Jurnal Ilmiah Pengembangan dan Penerapan IPTEKS, 2017)
The program aims to increase the community interest to local genetic wealth of Burgo chicken. The long term goal of this training is to make the village Sumber Rejo as centers of production, marketing and research activities of Burgo chicken. The method used in this service activity is a demonstration plot. The group is the group members who have been provided the knowledge and skills regarding the operation of the hatching machine. In the aspect of feed, farmers are given knowledge about the type of food, kathuk leaf supplement and ration formulation and feed mixing practices. This method is applied to support the acceleration of population growth of Burgo chicken. Extension and practice of using hatching machine, as well as kathuk leaf extract supplementation, also introduce to target farmer groups as a holistic effort in increasing Burgo chicken population. The implementation of this activity shows some facts that (1) Burgo chicken is relatively hard to find and can be sold at high prices. (2) During the culture treatment of feed that has been tested in previous studies, the production of eggs produced relatively high at an average of 48 eggs per head per egg-laying period, with low egg weight at an average of 35 grams per egg. (3) Power of hatching eggs based on observations is still in the good range at 41 %. (4) The DOC mortality rate reaches 50 %. Egg production data shows good potential. It can be seen from the total eggs produced within three months of culture (48 eggs) from five Burgo hens. High mortality and unmaximally hatchability will be increased along with the increasing skill in the culture farming and operation of the hatching machine. Key words: Burgo Chicken, Hatching, Katuk Leaf Extract, Revenue